2009
DOI: 10.1007/s12197-008-9074-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent evidence on the impact of government budget deficits on the ex ante real interest rate yield on Moody’s Baa-rated corporate bonds

Abstract: Ex Ante Real Interest Rate, Budget Deficits, Loanable Funds Model, E62, G12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Thus, it appears that after allowing for a variety of other factors, the higher the federal budget deficit (as a percent of GDP) the higher has been the nominal interest rate yield on 30 year fixed-rate home mortgages. This finding is consistent with a variety of empirical studies of earlier periods, including Al-Saji (1992, 1993, Barth, Iden and Russek (1984, Barth, Iden, Russek, and Wohar(1989), Cebula (1988Cebula ( , 1997, Cebula and Belton (1993), Cebula and Cueller (2010), Findlay (1990), Gissey (1999), Hoelscher (1986), Johnson (1992), Cebula & Saltz (1998), Tanzi (1985), and Zahid (1988).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, it appears that after allowing for a variety of other factors, the higher the federal budget deficit (as a percent of GDP) the higher has been the nominal interest rate yield on 30 year fixed-rate home mortgages. This finding is consistent with a variety of empirical studies of earlier periods, including Al-Saji (1992, 1993, Barth, Iden and Russek (1984, Barth, Iden, Russek, and Wohar(1989), Cebula (1988Cebula ( , 1997, Cebula and Belton (1993), Cebula and Cueller (2010), Findlay (1990), Gissey (1999), Hoelscher (1986), Johnson (1992), Cebula & Saltz (1998), Tanzi (1985), and Zahid (1988).…”
Section: Resultssupporting
confidence: 87%
“…It is expected that, in principle paralleling Russek (1984, 1985), Cebula (1988Cebula ( , 1997Cebula ( , 2005, Cueller (2010), andHoelscher (1986), the real domestic demand for long term bonds [mortgages, in this case] is a decreasing function of the expected future inflation rate, whereas the real domestic supply of long term bonds is an increasing function thereof. According to the conventional wisdom, the private demand for long term corporate bonds is a increasing function of Y, ceteris paribus, since as Y rises and the pace of real economic activity rises, and therefore economic agents are more willing and able to assume the risk associated with such bonds, as well as more able to afford to pay for same (Hoelscher, 1986;Cebula & Saltz, 1998;Cebula, 2005).…”
Section: Ndt+1 = the National Debt In Period T+1mentioning
confidence: 93%
See 1 more Smart Citation
“…The Ricardian equivalence hypothesis (Barro 1974(Barro , 1989 suggests that the effect of deficit-or debt-financed government spending is neutral in the long run. Feldstein (1982), Hoelscher (1986), Cebula (1997), Cebula and Cuellar (2010), Cebula (2014aCebula ( , 2014b, Cebula, Angjellari-Dajci, and Foley (2014) and others maintain that more government deficit/debt raises real interest rates and tends to crowd out spending by households and businesses. However, studies by McMillin (1986), Gupta (1989), Darrat (1989Darrat ( , 1990, Findlay (1990), and Ostrosky (1990) argue that more government deficit/debt would not raise the interest rate.…”
Section: The Modelmentioning
confidence: 99%
“…Research on the impact of state budget deficit on the rate of interest has also received extensive attention. In a study by Cebula and Cuellar (2009) using quarterly data for the period of 1973.1-2004.4 in the U.S., it is revealed that the federal budget deficit, expressed as a percent of GDP, has a positive and statistically significant impact on the ex-ante real interest rate yielded on Moody's Baa-rated corporate bonds. Plosser's (1982) study using U.S. data also indicates that the capital markets are not indifferent with respect to the level of government expenditures as higher interest rates are associated with increases in government purchases.…”
Section: Literature Reviewmentioning
confidence: 99%